Literature Review: Pengaruh Implementasi Green Marketing dalam Meningkatkan Minat Beli terhadap Produk Ramah Lingkungan - Muhammad Rafiedhia Brilliant Prayoga (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Green Marketing has emerged as a potent strategy for enhancing consumer awareness regarding environmentally friendly products, particularly in light of increasing concerns about sustainability. This research seeks to investigate the impact of Green Marketing on consumer purchase intentions and to pinpoint the challenges and opportunities associated with its implementation, utilizing the Systematic Literature Review (SLR) methodology. In practical terms, transparent and honest Green Marketing has been demonstrated to boost purchase intentions, whereas greenwashing erodes consumer trust. Additional elements such as brand trust and the utilization of social media further amplify the positive effects of Green Marketing. Nevertheless, the relatively higher costs of eco-friendly products continue to pose a significant obstacle, even as consumer awareness of environmental issues steadily rises. This study provides strategic insights for businesses in crafting and executing effective Green Marketing strategies by highlighting the significance of transparency, credibility, and genuine sustainability communication.